Talipes Equinovarus (TEV) and VACTERL Associated Anomalies: Narrative Literature Review - Huda Fajar Arianto; Faesal A Maodah; Yunus Abdul Bari (HM Publisher, 2022)
Clubfoot or known as Talipes Equinovarus (TEV), is a common anomaly in world population of newborn. This condition was reported in many studies as isolated anomaly but may come with other associated congenital anomalies. This review aims to further discuss the classification of TEV, its etiopathogenesis and how to diagnosis with all kind of VACTERL associated anomaly together with TEV. Many studies show a range of incidence between 1.1-4.5 per 1000 live birth per year and there is a chance of its condition followed by multiple congenital anomalies. Even though, this anomaly was an idiopathic condition, but still there is multifactorial etiology for its in which revealed through many studies also. Nevertheless, the orthopedic management of TEV with or without other congenital conditions still continue to develop to make a better improvement for the patients.